The role of ultraviolet light in the image and non-image forming visual systems of mice - Watson, T (2014)
Long thought to be absent from mammals, UV sensitivity has now been established in many species, including mice, where it has been found to provide visual sensitivity and drive circadian responses. Compared to closely related species, the murine UVS cone photopigment is both in relatively high abundance and is associated with a unique expression gradient across the retina, raising questions concerning the function of UV sensitivity that may be relevant to other mammals. Here we investigate the non-image and image forming roles of UV light in mice. Phase-shifting sensitivity changes in rod and cone photoreceptor mutants/ transgenics indicated a significant contribution by cone photoreceptors to this assay of photic-entrainment under UV light. Generation of an Opn1sw knockout lacking the UVS opsin gene confirmed a critical role of UVS cones in the non-image forming system of the mouse, differing from that established for the middle-wave sensitive (MWS) cone opsin, and confirmed that UV light could be used for visual tasks in a visual adaptation of the novel-object recognition assay. Finally, examination of retinal c-fos induction found evidence of an inhibitory influence of the cone pathway linked to short-wavelength sensitivity. That the contribution of UVS opsin was significantly greater than similar experiments have found for MWS cones, despite widespread cone opsin co-expression, may indicate a distinct role for the UVS-only s-cones in the non-image forming visual system. Overall these data suggest that the role of ultraviolet light in the circadian system of the mouse may be central to its unique cone opsin characteristics and provides new insight concerning this critical research model relevant to its use in the investigation of human biology.